Desafios da introdução das práticas ESG no âmbito empresarial - Inacio, Huanderson Luiz (Universidade Federal de São Carlos, 2023)
The present work brings an overview of business organizations and their different actions on ESG (Environmental, Social and Governance), showing different ESG concepts and metrics and how the connection between these three parts of a whole is intrinsic and need to walk together in order to reach the sustainability among themselves. Actions of an environmental nature will influence social well-being, but such actions will only be possible with competent governance, leading the Environmental Manager and Analyst to have a broadly distributed vision between these three concepts.
Challenges of introducing ESG practices in the business environment
Keywords: ESG; Gestão ambiental; Ambiente empresarial; Business organizations; Environmental management; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO::PLANEJAMENTO, PROJETO E CONTROLE DE SISTEMAS DE PRODUCAO